Bicultural individuals as workforce in Australian MNCs - Virtanen, Michèle-Martina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study focuses on bicultural individuals as workforce in multinational companies in Australia. The aim of the study is to research the role of these individuals in these companies, with three sub-questions; to research (bi)cultural identity biculturals have, exploiting biculturals’ competencies in multinational companies, and challenges in managing biculturals in these companies. The main theoretical concepts related to this research are biculture and a cross-cultural work environment. Furthermore, discussing biculturals as part of workforce in MNCs, by presenting opportunities and challenges, has been taken into account. The empirical part for the research was collected by semi-structured interviews between January and March 2016. The findings of this study suggest that the role of biculturals in MNCs is not established. Biculturals can be viewed as appreciated workforce but MNCs lack recognition and awareness of biculturals’ competencies. The competencies of biculturals’ are related to bicultural identity integration and sometimes competencies can be latent. Competencies bicultural individuals possess are often related to cultural knowledge, cultural frame switching, understanding and perception towards others. Australia as a nation faces cultural diversity daily but the potential behind it remains fairly untouched even on the individual level. The potential is everywhere but a more universal approach how to handle the potential still remains vague for most. There seem to be different approaches to diversity and to biculturalism, which lead to either advantage or challenge. It is found that in case the potential is recognized the result is more likely positive. Challenges may still occur yet if challenges are managed appropriately the company may be able to learn from them. Alternatively, ignorance is more likely to cause challenges that lead to a loss of resources. Biculturalism is not achieved overnight, as it was emphasized throughout this study, which highlights the role of competencies. For the future research it is necessary to find approaches how to enhance awareness and highlight possibilities, to capture currently lost potential.